VELOCITY: Pre-PCI Hypothermia Increases Adverse Event Rate without Reducing Infarct Size - Rizzo, Toni (MD Conference Express, 2014)
The Evaluation of Ultrafast Hypothermia Before Reperfusion in STEMI Patients trial [VELOCITY; NCT01655433] assessed the feasibility, safety, and efficacy of systemic hypothermia induced by peritoneal lavage in patients with STEMI prior to primary percutaneous intervention.